A Validated Method for Quantification of Dolutegravir Using Ultra Performance Liquid Chromatography Coupled With UV Detection. Issue 3 (June 2016) - Wang, Xinzhu; Penchala, Sujan Dilly; Amara, Alieu; Else, Laura; McClure, Myra; Boffito, Marta
Abstract : Background: Dolutegravir (DTG) is an integrase strand transfer inhibitor, which is a newly approved antiretroviral drug used for the treatment of HIV-infected naive and experienced individuals. Many aspects of DTG pharmacology remain to be studied. Our aim was to develop and fully validate a robust analytical method for the quantification of DTG in plasma using liquid chromatography coupled with UV detection. Methods: A simple and rapid protein precipitation method was used for analyte extraction from 100 µL plasma. The separation was achieved on a C8 reverse-phase analytical column using a gradient elution with 50 mmol/L formic acid and 50 mmol/L ammonium acetate in water (mobile phase A), and 100% acetonitrile (mobile phase B) and at a flow rate of 0.3 mL/min and a total run time of 10 minutes. The detector wavelength was set at 258 nm. Results: The linearity of the calibration curve (r > 0.9999, n = 6) was validated over a concentration range of 0.25–10 mcg/mL. Intra-assay variability ranged from 3.3% to 6.1% and inter-assay variability ranged from 4.5% to 5.7%. The overall accuracy ranged from 90.7% to 97.7% for the 3 different concentrations of quality control samples. Recovery efficiency of extraction ranged from 94.3%–100%. This method is highly selective with no interferences from commonly concomitant antiretroviral drugs or endogenous metabolites. Conclusions: The described method is simple, robust, selective, accurate, precise, and cost-effective. Thus, this assay can be readily transferred and implemented in clinical settings and used for pharmacokinetic studies and therapeutic drug monitoring programs.